Variations and influencing factors of soil organic carbon during the tropical forest succession from plantation to secondary and old–growth forest - Xing, Guitong; Wang, Xiaofang; Jiang, Yamin; Yang, Huai; Mai, Siwei; Xu, Wenxian; Hou, Enqing; Huang, Xingzhao; Yang, Qiu; Liu, Wenjie; Long, Wenxing (Frontiers in Ecology and Evolution, 2023)
Introduction Soil organic carbon (SOC) accumulation changed with forest succession and hence impacted the SOC storage. However, the variation and underlying mechanisms about SOC during tropical forest succession are not fully understood. Methods Soil samples at four depths (0–10 cm, 10–20 cm, 20–40 cm and 40–60 cm), litter, and roots of 0–10 cm and 10–20 cm were collected from three forest succession stages (plantation forest, secondary forest, and old– growth forest) in the Jianfengling (JFL) National Nature Reserve in Hainan Island, China. The SOC, soil enzyme activities, physiochemical properties, the biomass of litter and roots were analyzed. Results Results showed that forest succession significantly increased SOC at 0–10 cm and 10–20 cm depth (from 23.00 g/kg to 33.70 g/kg and from 14.46 g/kg to 22.55 g/kg, respectively) but not at a deeper depth (20–60 cm). SOC content of the three forest succession stages decreased with increasing soil depth and bulk density (BD). With forest succession from plantation to secondary and old–growth forest, the soil pH at 0–10 cm and 10–20 cm depth decreased from 5.08 to 4.10 and from 5.52 to 4.64, respectively. Structural equation model (SEM) results showed that the SOC at depths of 0–20 cm increased with total root biomass but decreased with increasing soil pH value. The direct positive effect of soil TP on SOC was greater than the indirect negative effect of decomposition of SOC by soil acid phosphatase (AP). Discussion To sum up, the study highlighted there was soil P– limited in tropical forests of JFL, and the increase in TP and total root biomass inputs were main factors favoring SOC sequestration during the tropical forest succession. In addition, soil acidification is of great importance for SOC accumulation in tropical forests for forest succession in the future. Therefore, forest succession improved SOC accumulation, TP and roots contributed to soil C sequestration.